A Study of the Changes in Human Resource Management Practices in LIC Due to the Impact of Private Insurance Players - Purohit, Sonal (Prabandhan: Indian Journal of Management, 2013)
The Government made a paradigm shift in the economic policy by adopting the process of liberalization, privatization, and globalization at the end of the previous decade. IRDA was set up as regulatory body and the private sector was allowed entry both in general and life insurance sector in India. Due to this impact, the private players came up with new and innovative marketing strategies. Due to these efforts of the private players, the benefits which LIC was enjoying due to its monopoly in the market were taken away, and it had to face tough competition to retain its market share. To fight this competition, LIC had to leave its traditional track and bring changes in its working. It has been widely accepted that the human resources of an organization are the key towards success. The present research paper throws light on the changes which LIC brought in its HRM policies due to the impact of the private insurance players. The changes brought by LIC in the agents’ recruitment, training, performance management system, and learning and development activities have been discussed in the present paper.